(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
The article studied the dynamics of the character of Botir communist, the main hero of Uzbek writer Toghay Murod’s novel of "One cannot die in this world". His actions motives controlled by religious views are analyzed on the basis of artistic text. The changes in the character’s nature were investigated on the basis of the dialectical unity of social and genetic factors. It was proved, that the hero’s dynamics is identified by the processes of his thinking and psychology.